Peterson's Graduate programs in the Biological Sciences (Thomson Peterson's, 2006)
This volume contains more than 4,000 programs of study in 45 disciplines of the biological sciences. Features and benefits include: * Informative data profiles for more than 4,000 graduate programs in 45 disciplines with facts and figures on accreditation, faculty, students, degree requirements, application deadlines, expenses, financial support and application contacts. * More than 600 two-page In-Depth Descriptions written by the institution give complete details on graduate study. * Advice on the admissions process, financial support, and accreditation and accrediting agencies. * Directories list programs in each volume. * Appendixes list institutional changes since the last edition and abbreviations used in the guide.